Review and Evaluation of Different Paint Booths Depending on Their Air Flow - Skėrys, Paulius (Jaunųjų mokslininkų darbai, 2018)
All companies aim to produce the best quality product and receive the highest profit. Also ensuring a healthy environment for employees is of high importance. Choosing the right type of spray booth will assure the latter in any company that is involved in painting. The article reviews and evaluates different airflow type spray booths. Using analysis of options the optimal decision is determined taking into account the price, simplicity of construction, paint finish quality, general spray booth size and energy consumption.
Keywords: paint booth; side draft; cross draft; downdraft; air flow